Analisis Peranan Pendidikan Untuk Membangun Karakter Bangsa Menghadapi Era Masyarakat Ekonomi Asean (MEA) - Ai Lisnawati; Selvi Novitasari; Tin Rustini (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The objectives of this research are: (1) Explanation of the role of education in building character, (2) Implementation of character education, (3) ASEAN Economic Community, (4) Challenges of education in the ASEAN Economic Community (AEC), (5) Character education is a solution for entry into force (MEA). The ASEAN Economic Community (AEC) asks Indonesians to have a very enthusiastic mentality when dealing with people from other countries. One of the efforts to form an Indonesian nation with an extraordinary spirit is education. creating good personality values that are implemented in individual personalities that will support the desired national character. The most important thing is to practice it in a real way in life. Therefore, the role of education is very necessary and important in building the character of a nation that is good and good at facing the threat of globalization, as is regulated in Article 3 of Decree Law Number 20 of 2003 regarding the National education system which states that national education has the function of building skills, creating character and the existence of a dignified civilization of a nation in order to make the nation's life more intelligent. Therefore, the role of good and good education will help Indonesia survive, build and create identity to develop competitiveness with the ASEAN Economic (AEC).